2012
DOI: 10.3390/ijerph9030772
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Suicide and Other Trespassing Fatalities on State-Owned Railways in Greater Stockholm; Implications for Prevention

Abstract: Each year, approximately 80–100 people are killed on state-owned railways due to train-person collisions in Sweden. Underlying causes are suicide and accidents; suicide constituting a vast majority. Earlier Swedish studies at a national level revealed a relation between population density and incident frequency, however, with places of occurrence often located to the outskirts of cities some distance away from station areas where victims can await approaching trains in seclusion. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
(30 reference statements)
5
8
0
6
Order By: Relevance
“…The safety operation of remaining LCs should be improved by ensuring appropriate physical conditions and sufficient warnings (Ozdo gan et al, 2006), as well as active warning devices (Evans, 2011;Savage, 2006). Redesigning LCs to increase visibility is recommended to prevent suicide (Rådbo et al, 2012) and trespass (Horton, 2009;Silla and Kallberg, 2012), allowing pedestrians to be detected more easily if they enter the tracks illegally from a LC. The least safe LCs -the passive ones -should be designed is such ways that pedestrians are able to judge whether or not it is safe to enter the tracks (BTRE, 2002).…”
Section: Environmental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety operation of remaining LCs should be improved by ensuring appropriate physical conditions and sufficient warnings (Ozdo gan et al, 2006), as well as active warning devices (Evans, 2011;Savage, 2006). Redesigning LCs to increase visibility is recommended to prevent suicide (Rådbo et al, 2012) and trespass (Horton, 2009;Silla and Kallberg, 2012), allowing pedestrians to be detected more easily if they enter the tracks illegally from a LC. The least safe LCs -the passive ones -should be designed is such ways that pedestrians are able to judge whether or not it is safe to enter the tracks (BTRE, 2002).…”
Section: Environmental Designmentioning
confidence: 99%
“…Holdaway et al, 2012;Lindberg, 2012;Rådbo and Andersson, 2012), publications that provide some sort of recommendations and others focus on rich technical details, for example about the implementation of closed-circuit television (CCTV). In most cases the systems are recommended to detect (and sometimes warn) the persons at risk.…”
Section: Monitoring and Detection Systemsmentioning
confidence: 99%
“…A análise das estatísticas de acidentes ferroviários sugere que estes são mais propensos a envolver transgressores (isto é, usuários, pedestres ou veículos, que estão ilegalmente no corredor ferroviário) (PELLETIER, 1997;TERRY, 2003;LOBB, 2006;LUOMA, 2009 Embora acidentes relacionados a trens e pedestres sejam relativamente subdiscutidos, essas falhas constituem uma considerável parcela de mortes e ferimentos em acidentes relacionados a ferrovias (PELLETIER, 1997;TERRY, 2003, SILLA;LUOMA, 2009;LUOMA, 2012;ANDERSSON, 2012). Além disso, esses acidentes anualmente demandam bilhões de dólares em custos diretos e indiretos (GOLDBERG; MOOTHA; LINDSEY, 1998;TROTTENBERG;RIVKIN, 2013;SOUSA et al, 2014;ZHAO;IRANITALAB;.…”
Section: As Passagens Na Linha Férrea E a Sua Relação Com Os Atropelaunclassified
“…Diante disso, esta pesquisa se concentra nos acidentes envolvendo pedestres e veículos ferroviários, ou seja, atropelamentos ferroviários. Embora esses incidentes sejam relativamente pouco discutidos (RÅDBO; ANDERSSON, 2012;ZHANG et al, 2018), constituem uma considerável proporção de mortes e ferimentos (PELLETIER, 1997;LUOMA, 2012;ANDERSSON, 2012;FRA, 2015;STEFANOVA et al, 2018;ZHANG et al, 2018).…”
Section: Introductionunclassified
“…A small percentage (14.5%) jumped in front of the train from a platform or ran in front of the train. Another study [6] found that 36% walked along the rails and 30% laid down on the rail, and another 30% jumped or ran in front of the train. In Finland, half of suicide attempters waited for the train on the tracks and 18% jumped or ran in front of the train [7].…”
Section: Introductionmentioning
confidence: 99%